1999
DOI: 10.1111/j.1745-4522.1999.tb00148.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Peroxide Value in Crude Palm Oil Products Using Fourier Transform Infrared Spectroscopy

Abstract: A rapid Fourier transform infrared (FTIR) spectroscopic technique coupled with fixed NaCl cell (1 mm pathlength) was developed to measure peroxide value (PV) in crude palm oil (CPO) and crude palm kernel oil (CPKO). Calibration standards were prepared by oxidizing CPO in a fermentor at 60C over a period of 24 h. A partial least squares (PLS) calibration model for predicting PV was developed based on the 3710–3210 cm‐1spectral region with reference to a single‐point baseline at 3710 cm‐1. The optimization of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…The hydroperoxide bands have been reported at 3450 cm -1 , due to -OO-H stretching vibration of the oxidized methyl octadecadieonate [4]. The formation on hydroperoxide band however was not observable in this study.…”
Section: Quantitative Analysis Of Peroxide Value In Virgincontrasting
confidence: 56%
See 2 more Smart Citations
“…The hydroperoxide bands have been reported at 3450 cm -1 , due to -OO-H stretching vibration of the oxidized methyl octadecadieonate [4]. The formation on hydroperoxide band however was not observable in this study.…”
Section: Quantitative Analysis Of Peroxide Value In Virgincontrasting
confidence: 56%
“…(1) shows the FTIR spectrum of VCO. One of the main feature of the spectrum is in the region of 3050 to 2800 cm -1 which was attributed to the absorbance of CH stretching vibrations (cis-CH=CH-, -CH 2 -, CH 3 , CH 2 /CH 3 ) [4]. The region between 1400 to 900 cm -1 is due to the stretching of C-O-C and CH bending [7].…”
Section: Spectra Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that flaxseed oil had a PV value of 0.24 (Jaswir, Kitts, Che Man, & Hassan, 2005), which was lower than those determined in the commercial oils, such as olive (3.37), castor (0.46), and soybean oil (0.5) (Miyasawa, Fujimoto, Kinoshita, & Usuki, 1994;Moh & Stang, 1999;Vekiari, Papadopoulou, & Kiritsakis, 2007), which reflects the low PV value in the flaxseed-added tortilla. The low PV value is an additional characteristic of the flaxseed-added tortilla, because it can be stored for a longer time with no rancidity problems and with soft texture.…”
Section: Peroxide Values (Pv)mentioning
confidence: 72%
“…The high level of FFAs in CPO indicates its lower ability due to the enzymeic and microbial lipase reactions of palm fruit, as well as the storage of CPO under bad conditions such as high temperature and high moisture which can affect the quality of oil [9,10]. The most commonly used methods for FFA separation are molecular distillation, chemical esterification, supercritical extraction, and organic solvent nanofiltration [11,12].…”
Section: Introductionmentioning
confidence: 99%